Gesteuerte Erwerbsmigration nach Deutschland - David Adunts; Herbert Brücker; Tanja Fendel; Andreas Hauptmann; Sekou Keita; Regina Konle-Seidl (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
Prognosen zufolge würde das Erwerbspersonenpotenzial ohne Wanderungen bis 2060 um rund ein Drittel sinken. Zu seiner Stabilisierung ist der deutsche Arbeitsmarkt in den kommenden Jahren vor allem auf die Einwanderung aus Drittstaaten angewiesen. Mit 10 Prozent aller Zuzüge spielt die Einwanderung aus Drittstaaten in Deutschland im Gegensatz zu Einwanderungsländern wie Kanada, Australien und Neuseeland jedoch nur eine untergeordnete Rolle im Wanderungsgeschehen. [...] – – According to forecasts, the labour force potential would fall without migration by around one- third until 2060. Therefore, the German labour market will likely rely heavily on labour migration from third countries to stabilize the labour force potential in the coming years. However, in Germany, labour migration accounts for only 10 percent of all immigration from third countries. In contrast, in traditional immigration countries such as Canada, Australia, and New Zealand, the share of labour migration varies from 30 to 40 percent. This low share of labour migrants in Germany is partly due to minimum criteria that guide the system of managing labour migration. Since these criteria all have to be met at the same time, they can have a restrictive effect. Therefore, a reassessment of the minimum legal criteria for labour migration is required to increase the influx of skilled workers. [...]
Keywords: 330; Erwerbspersonen; Erwerbsmigration; Fachkräfte; Arbeitsmarktitegration